NARRATIVA TRANSMEDIA: ANÁLISIS DE LA PARTICIPACIÓN DE LA AUDIENCIA EN LA SERIE 13 REASONS WHY PARA LA APROXIMACIÓN AL TEMA DEL SUICIDIO - Mgt. Tomás ATARAMA-ROJAS,Bach. Selene REQUENA ZAPATA (Fonseca, Journal of Communication, 2023)
The production and circulation of audiovisual products has changed thanks to the transmedia narrative. One of the main characteristics of this narrative is the active participation of the audiences. This article analyzes the use of the transmedia strategies of the series 13 Reasons Why to explore whether the participation, dialogue and debate of the audience can be fostered through it for an approach to sensitive topics such as suicide, the main theme main of the series. The results show that the transmedia narrative allows a more complete approach to sensitive topics based on interaction with the audience.